PHONETIC FEATURES CHARACTERISTIC OF THE KHOREZM DIALECT IN THE WORK “DEVONU LUGOTIT-TURK” (TAMADDUN NURI JURNALI, 2024)
In the article, the phonetic features of the work “Devonu lugotitturk” are studied in depth, the manifestations of this language level in the work in the Khorezm Oghuz and Kipchak dialects of the Uzbek language are analyzed in detail, and this opinions are held in the village. Also, lexical units in the dialect are compared with the work “Attuhfa”. A number of linguistic methods, such as comparison, comparativehistorical, were effectively used in the analysis of examples.